Mannan oligosaccharide as an alternative to infeed antibiotics to improve growth performance of broilers: a meta-analysis - Polidoro, B. R. [UNESP]; de Oliveira, M. J.K.; Braga, F. D.S.C. [UNESP]; Polycarpo, G. D.V. [UNESP] (Taylor & Francis, 2025)
1. The purpose of this meta-analysis was to evaluate the effect of mannan oligosaccharide (MOS) as an alternative to antibiotic growth promoters (AGP) on feed intake (FI), body weight gain (BWG), and feed conversion ratio (FCR) of broilers. 2. Data from 75,594 broilers were extracted from 17 articles (19 trials) published between January 2010 and March 2023. The main criteria for the publication selection were as follows, at least three treatments applied (negative control group without MOS or AGP versus MOS or AGP supplementation), presence of performance results, and intra-experimental variation associated with the mean of response (such as standard error). Treatments were classified as control, MOS, or AGP, and adjusted means of treatment were compared. Additionally, the average daily gain (ADG) and average daily feed intake (ADFI) of each type of supplementation were calculated relative (Δ) to the control group (ΔADFI and ΔADG) and expressed as a percentage of the difference. 3. Broilers receiving a diet supplemented with MOS had a 3.7% better BWG and 3% better FCR compared to the control diet (P < 0.001), but these variables were similar to the group receiving AGP supplementation. No significant difference was detected in FI among treatments (P > 0.050). The relationship between ΔADG and ΔADFI was linear for the MOS and AGP-supplemented group (P < 0.050). The ΔADG of broilers fed diets supplemented with MOS or AGP was 6.4% and 4.54% when ΔADFI was zero, respectively. The ΔADG of MOS increased by 0.58% for every 1% of increasing observed in ΔADFI. The corresponding value for the increased ΔADG for the AGP group was 0.69%. 4. The results of this meta-analysis indicated that MOS supplementation is effective in increasing BWG and reducing FCR, similar to broilers fed a diet supplemented with AGP. Therefore, MOS is a safe and sustainable alternative for AGP-free poultry production.
Keywords: Chicken; feed additive; mannanoligosaccharide; MOS; poultry; prebiotic; saccharomyces cerevisiae; yeast cell wall